Benefit–risk assessment of paliperidone oral extended-release tablet versus monthly injectable for maintenance treatment of schizophrenia. (November 2016) - Levitan, Bennett; Markowitz, Michael; Turkoz, Ibrahim; Fu, Dong-Jing; Gopal, Srihari; Alphs, Larry
Abstract : The purpose of this study was to conduct a post-hoc benefit–risk assessment of paliperidone palmitate once-monthly (PP1M) injectable versus oral paliperidone extended-release (ER) in schizophrenia maintenance treatment. The Benefit–Risk Action Team framework was used to structure the analysis based on patient-level data from two similar, double-blind, placebo-controlled relapse studies. Efficacy outcomes were relapse, psychiatric hospitalization, Clinical Global Impression–Severity scale, Personal and Social Performance (PSP) scale, and Positive and Negative Syndrome Scale (PANSS). Safety outcomes were extrapyramidal symptom–related adverse events, weight gain, prolactin-related adverse events, somnolence, orthostatic hypotension, anticholinergic use, fasting plasma glucose, and total cholesterol/high–density lipoprotein. For the first 8 weeks of maintenance treatment, most efficacy outcomes significantly favored PP1M compared with paliperidone ER. Per 1000 patients, there would be 165, 115, 85, and 53 fewer cases of PSP worsening, relapse, PANSS worsening, and hospitalizations, respectively. For the first 40 weeks, PSP worsening significantly favored PP1M (140 fewer cases). Relapse, PANSS, hospitalizations, and Clinical Global Impression–Severity scale showed a consistent pattern favoring PP1M but were not significant. Safety outcomes for both 8-week and 40-week periods demonstrated no statistically significant differences between groups. These analyses suggest a benefit–risk profile favoring PP1M over oral paliperidone ER throughout 40 weeks of treatment, particularly in early treatment.